Engaging Stakeholders in the Aquaculture Business Incubation Space – Expeditions of ICAR-CIBA from 2002–20 - Ravisankar, T; Patil, P K; Geetha, R; Vinoth, S; Sairam, C V; Vijayan, K K (Indian Farming, 2020)
Brackishwater aquaculture has been a dependable subsector of fisheries for food, employment, and prosperity through export earnings since the 1980s. The export of shrimps has superseded the export of all agricultural commodities, taken individually, in 2018-19. From 1.91 billion (` 8,607.94 crore) in 2008-09, India’s marine exports increased to 7.08 billion (` 45,106.89 crore) in 2017-18 which includes 4.85 billion (` 30,868.17 crore) from frozen shrimps. About 90 per cent of shrimp exports are today from Pacific White Shrimp. In a decade, shrimp production had gone up more than nine times to roughly 7 lakh tonnes, of which the share of Penaeus vannamei was 6,23,000 tonnes. Ensuring the supply of quality seeds, feed, and other farm inputs is the key to the continued success of the sector.